2006
DOI: 10.1016/j.jmedhist.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Least of the laity: the minimum requirements for a medieval Christian

Abstract: This article investigates the minimum level of religious observance expected of lay Christians by church authorities, and the degree to which legislation and procedures attempted to enforce these standards. 1 Once baptized, a person entered the community of the faithful; and the medieval church was as much accountable for the health and salvation of the ignorant, the ambivalent, the disobedient or distracted as they were of the devout. From the twelfth century, theologians, clerical authorities and the laity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…A considerable motivation for marine food consumption existed as the Roman Catholic Church, like the Eastern Orthodox Church, regularly imposed dietary restrictions on its faithful. Fasting regulations varied over time and by social class, but the basic point was a prohibition on the consumption of meat at many times during the year including Fridays and Lent (Henisch, 1976;Bazell, 1997;Tanner and Watson, 2006).…”
Section: Marine Foods In Byzantine Andmentioning
confidence: 99%
“…A considerable motivation for marine food consumption existed as the Roman Catholic Church, like the Eastern Orthodox Church, regularly imposed dietary restrictions on its faithful. Fasting regulations varied over time and by social class, but the basic point was a prohibition on the consumption of meat at many times during the year including Fridays and Lent (Henisch, 1976;Bazell, 1997;Tanner and Watson, 2006).…”
Section: Marine Foods In Byzantine Andmentioning
confidence: 99%
“…For example Norman Tanner and Sethina Watson have argued that although medieval churchmen had high aspirations for the laity, they were also willing to tolerate ignorance, in a pragmatic attempt to keep as many people within the church as possible. 1 This and some other surveys of medieval religion have also suggested that for many medieval Christians, as long as they accepted some core beliefs, religion was more about participating in the rituals than about having a high level of doctrinal knowledge. 2 While broad surveys like these have often (although not always 3 ) emphasised low expectations of knowledge and the importance of ritual, more narrowly focused studies offer a different picture, especially for the fourteenth and fifteenth centuries.…”
mentioning
confidence: 83%
“…1 This and some other surveys of medieval religion have also suggested that for many medieval Christians, as long as they accepted some core beliefs, religion was more about participating in the rituals than about having a high level of doctrinal knowledge. 2 While broad surveys like these have often (although not always 3 ) emphasised low expectations of knowledge and the importance of ritual, more narrowly focused studies offer a different picture, especially for the fourteenth and fifteenth centuries. Numerous studies of English parishes in this period have shown that at least some laypeople had a good understanding of Christianity as well as participating enthusiastically in parish rituals.…”
mentioning
confidence: 83%
“…The highest form of Christian prayer is contemplative prayer, which consists in deep intimacy of the devotee with God, a personal relationship 8 (Vauchez 1993, pp. 104-105;Webb 2005, p. 28;Tanner and Watson 2006). The prescriptions of the fourth Lateran Council involve strengthening the role of parishes in the Middle Ages.…”
Section: Of 33mentioning
confidence: 99%